The German Joyce - Weninger, Robert (Florida James Joyce series., 2012)
In August 1919, a production of James Joyce's Exiles was mounted at the Munich Schauspielhaus and quickly fell due to harsh criticism. The reception marked the beginning of a dynamic association between Joyce, German-language writers, and literary critics. It is this relationship that Robert Weninger analyzes in The German Joyce. Opening a new dimension of Joycean scholarship, this book provides the premier study of Joyce's impact on German-language literature and literary criticism in the twentieth century. The opening section follows Joyce's linear intrusion from the 1910s to the 1990s by.